“Going above and beyond” for implementation in the education sector: extension and validation of the School Implementation Citizenship Behavior Scale (SICBS) - Catherine M. Corbin; Mark G. Ehrhart; Eric C. Brown; Jill Locke; Clayton R. Cook; Gregory A. Aarons; Aaron R. Lyon (Implementation Science Communications)
Abstract Background Employee behaviors that strategically support implementation (i.e., implementation citizenship behavior [ICB]) theoretically promote the adoption and high-fidelity use of evidence-based practices (EBPs). ICB (e.g., helping colleagues overcome implementation barriers) may vary across contexts, including schools where children are most likely to access and receive mental and behavioral health services. Pragmatic measures are needed to advance nascent research on school-based ICB and inform how these behaviors can be used to support successful implementation. The current study expanded the Implementation Citizenship Behavior Scale (ICBS) to create and validate the School Implementation Citizenship Behavior Scale (SICBS) in a sample of elementary school teachers implementing evidence-based prevention programs to support children’s mental and behavioral health. Methods Based on subject matter expert feedback, items were refined from the original ICBS and items for two new subscales (taking initiative, advocacy) were created for the SICBS. A sample of 441 public school teachers from 52 elementary schools in the Midwest and Western United States of America completed a survey that included the SICBS and additional measures to assess convergent and divergent validity. SICBS was refined and validated via examination of item characteristics curves to reduce items and develop a pragmatic instrument, confirmatory factor analyses to evaluate the hypothesized measurement structure, and assessment of convergent and divergent validity. Results The original two ICBS subscales (helping others, keeping informed) were retained, and two new three-item subscales resulted from item reduction analyses (taking initiative, advocacy). The hypothesized second-order factor model was generally well fit to the data (CFI = .99, TLI = .99, RMSEA = .09), all first- (λs = .85-.96) and second-order factor loadings (λs = .93-.95) were high. All SICBS subscales demonstrated acceptable reliability (αs = .88-.92). Convergent validity was evidenced by moderate correlations with organizational citizenship behavior items (rs = .42-.49). Divergent validity was demonstrated by weak correlations with teachers’ beliefs about teaching (rs = .31-.38) and null correlations with most school demographics. Conclusion Results support the structural, convergent, and divergent validity of the 12-item, 4-factor SICBS. The SICBS provides a deeper understanding of individual implementer actions that may serve as implementation mechanisms or outcomes.